Pneumonia hospitalizations and the subsequent risk of incident ischaemic cardiovascular disease in Chinese adults. (7th April 2021) - Hu, Yizhen; Yu, Canqing; Guo, Yu; Bian, Zheng; Han, Yuting; Yang, Ling; Chen, Yiping; Du, Huaidong; Pang, Yuanjie; Sun, Dianjianyi; Jin, Jianrong; Zhang, Jun; et al.
Abstract: Background: Acute respiratory infections have been associated with a transient increase in cardiovascular risk. However, whether such an association persists beyond 1 month and the potential modifying effect of cardiovascular risk factors on such an association are less well established. Methods: The China Kadoorie Biobank enrolled 512 726 participants aged 30–79 years from 10 areas across China during 2004–2008. By the end of 2017, a total of 5444 participants with new-onset ischaemic heart disease (IHD) and 4846 with ischaemic stroke (IS) who also had at least a record of hospitalization for pneumonia during follow-up were included. We used a self-controlled case-series method and calculated the age- and season-adjusted relative incidences (RIs) and 95% confidence intervals (CIs) for ischaemic cardiovascular disease (CVD) after pneumonia. Results: The risk of ischaemic CVD increased during days 1–3 after pneumonia hospitalization, with an RI (95% CI) of 4.24 (2.92–6.15) for IHD and 1.85 (1.02–3.35) for IS. The risk gradually reduced with longer duration since pneumonia hospitalization but remained elevated until days 92–365 for IHD (1.23, 1.12–1.35) and days 29–91 for IS (1.25, 1.05–1.48). Pre-existing cardiovascular risk factors amplified the associations between pneumonia and ischaemic CVD risks, such as chronic obstructive pulmonary disease for both IHD and IS, and diabetes and smoking for IHD (all P interaction  < 0.05). Besides, the risk of ischaemic CVD was also higher among the participants aged ≥70 years ( P interaction  < 0.001 for IHD and 0.033 for IS). Conclusion: Among middle-aged and older Chinese adults, pneumonia hospitalization was associated with both short- and long-term increases in ischaemic CVD risk for ≤1 year.